“High the Mountain, Long the River”: Chinese Landscape Painting and Its Afterlife in the Short Animation Film "Feeling from Mountain and Water" (1988) - Chen, Yuxin (The Columbia Journal of Asia, 2022)
In 1988, the Shanghai Animation Film Studio produced a 19-minute short film Shanshui qing 山水情, known in English as Feeling from Mountain and Water. Devoid of dialogue, the film recounts the friendship between an elderly musician and a young fisherwoman. The last of the Studio’s ink-wash animation project, Feeling from Mountain and Water transfers the visuality of traditional Chinese landscape paintings to the cinematic format. My paper focuses on this market-reform-era production and examines the little-discussed afterlife of landscape art in the medium of animation. Conjoining visual analyses, animators’ self-accounts, and existing literature on 20th-century Chinese art, I aim to resituate Feeling from Mountain and Water in the historical juncture when it was created. Specifically, I argue that instead of a forced resurrection of traditional aesthetic, the film belongs to an unbroken artistic lineage in the Chinese landscape tradition, complicates the issue of “the artist’s hand” in Chinese pictorial art, as well as reflects the ever-changing political and economic climate from the Republican era to the age of the market reforms.